ROTC Commissioning Ceremony in Goddard Chapel during the weekend of the 2005 Commencement. Photo 038 - Schutzengel, Aaron (Tufts Archival Research Center, 2008)
ROTC Commissioning Ceremony in Goddard Chapel during the weekend of the 2005 Commencement.